THE ANALYSIS OF STUDENTSâ MOTIVATION IN LEARNING ENGLISH AS AN EFL ON DOUBLE-DEGREE PROGRAM OF FOREIGN LANGUAGE ACADEMY (ABA-YW UMI MAKASSAR) - Burhanuddin, - (ELT WORLDWIDE, 2015)
The aim of this research was to analyze and to find out (i) the types of studentsâ motivation in learning English as an EFL on Double-Degree program of Foreign Language Academy (ABA-YW UMI Makassar, South Sulawesi) where the Double-Degree program is applied, (ii) how the motivation emerged in the classroom during the teaching and learning processes, and (iii) the studentsâ perceptions of Double-Degree program and the impact to their achievements. The students of Moslem University of Indonesia have time and opportunity to study on Double-Degree program through the foreign Language academy (ABA YW-UMI Makassar) since 2009. The researcher used the descriptive qualitative method. The data were collected from four respondents of the Academy. The instrument of the research is the researcher himself. The researcher did the classroom observation, observation sheets, list of questions, recorded video and interview photo. The researcher carried out the observation and semi structured-interview in collecting the data. And then the researcher followed the steps in data analyzing they are: reading memoing, describing and classifying. The results of the research showed that (i) most of the respondents had the integrative motivation in learning a foreign language (English), (ii) the studentsâ motivation emerged in the classroom during the teaching and learning processes when they met and exchange ideas in the classroom from the different majors or faculties, and (iii) their perceptions on the Double-Degree program and its applications, and the impact to their achievements were high/positives and they believed that by having the two degrees or skills, they will be easy to apply and to finding jobs, status, and career. The theory related to the research is the socio-educational theory and motivational views theory, they are: self-determination theory, goals theory and attribution theory. Learnersâ motivation to these theories in order to receive externally administered rewards: praise, gold starts, grade, certificate, diplomas, scholarship, financial independence, and ultimate happiness Key words : Analysis of LLM, Motivation in learning EFL, Integrative and Instrumental Motivations in EFL